Equilibrium Subprime Lending - MAKAROV, IGOR; PLANTIN, GUILLAUME (Journal of Finance, 2013)
ABSTRACT This paper develops an equilibrium model of a subprime mortgage market. Our goal is to offer a benchmark with which the recent subprime boom and bust can be compared. The model is tractable and delivers plausible orders of magnitude for borrowing capacities, as well as default and trading intensities. We offer simple explanations for several phenomena in the subprime market, such as the prevalence of teaser rates and the clustering of defaults. In our model, both nondiversifiable and diversifiable income risks reduce debt capacities. Thus, debt capacities need not be higher when a larger fraction of income risk is diversifiable.